Batik Dengan Pewarna Alami Upaya Meraih Pasar Wisatawan Mancanegara - Winarsih, Atik Septi; Zaenuri, Muchamad; Asnawi, Asnawi (Universitas Muhammadiyah Yogyakarta, 2018)
Batik Indonesia has been confirmed by Unesco as a world cultural heritage and Yogyakarta was crowned as World Batik City by World Craft Council (WCC), on the 50th anniversary of the organization in Dongyang, Zhejiang Province, China, on October 18-23, 2014 This indicates that batik is worldwide. Batikpun usage rate is very high, not only the people of Indonesia but also many foreign tourists who buy batik for souvenirs even batik also has become an export product. Yogyakarta Special Region (DIY) is a tourist visiting area that relies on batik as main souvenir. Production of batik in Yogyakarta is high enough to cause environmental problems, especially in the disposal of waste. The process of making this batik will harm or disrupt the natural environment around, such as plants and animals and even livestock. Environmental disturbances are based on substances or chemicals released at the end of the batik making process. By looking at these conditions began to be thought by the batik craftsmen to develop environmentally friendly batik by using natural dyes. The use of natural dyes is not so popular and still at the stage of testing, but Mrs. Rini Kartikasari and Mrs. Tanti Syarif have started introducing this product to the market. The main issue of course relates to the marketing and governance of the development of this natural dye batik. With this PPPE program can make batik natural dyes as export products or can be marketed in the areas of foreign tourists visit. At the present stage, several activities have been conducted, such as: partners and their communities have received tourism management training, upgraded showroom, and assistance for exhibition, website design and equipment introduction. In this year also generated output in the form of: standardization of product quality, website, and various equipment to support batik production process with natural dye. From these activities bring significant benefits for both partners, they are able to increase sales turnover and can market products in the area of â€ foreign tourists.Keywords: batik, natural dye, Sleman.